HUBUNGAN MEKANISME KOPING DENGAN TINGKAT KECEMASAN PENULARAN COVID-19 PADA MASYARAKAT DESA KUDUGEDE - Reza Dewi Lestari; Cecep Heriana; Rany Muliany Sudirman (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2021)
Background: COVID-19 has affected more than 2-3 million people in 185 countries around the world. Based on the number of COVID-19 cases in Kuningan Regency, there were 16.482 cases and in Kadugede District there were 25 cases. The high rate of transmission of the COVID-19 virus causes anxiety among the public. Coping with anxiety levels well requires a coping mechanism. The purpose of this study was to determine the relationship between coping mechanisms and the level of anxiety regarding the transmission of COVID-19 in the people of Kadugede Village, Kadugede District, Kuningan Regency in 2021. Methods: The type of research used was quantitative analytical cross sectional. The total population in this study was 4521 people with a sample of 98 respondents taken using thetechnique Proportionate Stratified Random Sampling. The instrument used is a questionnaire, with an assessment of thestatistical test Spearman rank. Results: The results showed that most of respondents had maladaptive coping mechanisms (51%) and almost most of the respondents had very severe levels of anxiety (39.8%). The results of statistical tests with the spearman rank test showed pvalue = 0.003. Conclusion: There is a significant relationship between coping mechanisms and the level of anxiety regarding the transmission of COVID-19 in the people of Kadudege Village, Kadugede District, Kuningan Regency in 2021, with p value = 0.003.Suggestion: Are expected that the community can reduce anxiety levels with good coping mechanisms.